Estado e sociedade da informação no Brasil: uma investigação sobre o papel da informação na gestão pública - Malin, Ana Maria Barcellos (2003)
In the 80 s and 90 s the reform of the nation state became part of the agenda of governments from all over the world, reflecting changes in social demands. New ways of public management are then sought, adopting management criteria of decentralization and governance among others. These new ways of public management require more manageable information environment, involving more actors thus becoming more complex and technology oriented. This research deals with these factors concluding that public management condition and is conditioned by the government environment of information. Despite the obviousness of this affirmation, few are the works that discuss the consequences of lack of interaction between one and the other. Taking into consideration specific characteristics from Brazilian political culture, this research point to the need to restore the deficit of past actions in informational field lined up with the Brazilian s State capacity to respond to society s claim. Some activities from urban public management from the city of Rio de Janeiro are taken as illustrative example without generalizing it's conclusion